HDFS-oriented cryptographic key resource control mechanism - Wei JIN; Fenghua LI; Mingjie YU; Yunchuan GUO; Ziyan ZHOU; Liang FANG (Tongxin xuebao)
The big data environment presents the characteristics of multi-user cross-network cross-access, multi-service collaborative computing, cross-service data flow, and complex management of massive files.The existing access control models and mechanisms are not fully applicable for big data scenarios.In response to the needs of fine-grained access control and multi-service strategy normalization for cryptographic data in the big data environment, starting from the scene elements and attributes of access control, the HDFS-oriented CKCM was proposed by mapping the cyberspace-oriented access control (CoAC) model.Subsequently, a fine-grained access control management model for HDFS was proposed, including management sub-models and management supporting models.The Z-notation was used to formally describe the management functions and management methods in the management model.Finally, the CKCM system was implemented based on XACML to realize fine-grained secure access control for managing file and secret keys in HDFS.